Peutz-Jeghers syndrome. Issue 3 (May 2021) - Tacheci, Ilja; Kopacova, Marcela; Bures, Jan
Abstract : Purpose of review: Peutz-Jeghers syndrome is a rare, autosomal dominant, hereditary polyposis syndrome defined by gastrointestinal hamartomas and mucocutaneous pigmentations, caused by a germline mutation in the serine/ threonine kinase 11 or liver kinase B1 (STK11/LKB1) genes. Hamartomatous polyps located throughout the gastrointestinal tract can be complicated by bleeding and small bowel intussusception, potentially leading to the need for emergency surgery. Individuals suffering from Peutz-Jeghers syndrome have an increased lifetime risk of various forms of cancer (gastrointestinal, pancreatic, lung, breast, uterine, ovarian and testicular). Surveillance should lead to the prevention of complications and thus a reduction in mortality and morbidity of patients. Recent findings: A combined approach based on wireless capsule endoscopy, magnetic resonance enterography and device-assisted enteroscopy is effective in reduction of the polyp burden and thus decreasing the risk of bleeding and intussusception. Current guidelines for screening and surveillance are mostly based on expert opinion rather than evidence. Summary: Peutz-Jeghers syndrome is an emerging disease that significantly affects the quality of life enjoyed by patients. Despite of all the progress in improved early diagnostics, options for advanced endoscopic therapy and elaborate surveillance, acute and chronic complications decrease the life expectancy of patients suffering from Peutz-Jeghers syndrome.